2010
DOI: 10.1021/bi1009503
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Selection of DNA Thioaptamers Targeted to the HA Binding Domain of Human CD44

Abstract: CD44, the primary receptor for hyaluronic acid, plays an important role in tumor growth and metastasis. CD44-hyaluronic acid interactions can be exploited for targeted delivery of anti-cancer agents specifically to cancer cells. Although various splicing variants of CD44 are expressed on the plasma membrane of cancer cells, the hyaluronic acid binding domain (HABD) is highly conserved among the CD44 splicing variants. Using a novel two-step process, we have identified monothiophosphate-modified aptamers (thioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 48 publications
1
60
0
1
Order By: Relevance
“…Somasunderam et al (2010) reported the selection of ssDNA thioaptamers that can bind hyaluronic acid binding domain of the CD44 receptor. The results of this study showed that the selected thioaptamers did bind the CD44 protein with a higher affinity (180-295 nM) compared with hyaluronic acid (K d > 61 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Somasunderam et al (2010) reported the selection of ssDNA thioaptamers that can bind hyaluronic acid binding domain of the CD44 receptor. The results of this study showed that the selected thioaptamers did bind the CD44 protein with a higher affinity (180-295 nM) compared with hyaluronic acid (K d > 61 mM).…”
Section: Discussionmentioning
confidence: 99%
“…These aptamers bind specifically to CD44-expressing tumor cells with high efficacy. However, the in vivo bioavailability of these aptamers has not been examined in detail (Somasunderam et al, 2010). …”
Section: Targeting Ha Receptorsmentioning
confidence: 99%
“…It is possible that for these cells that it binds to different peptide/proteins compared with the CCRF-CEM target cells, and the binding of these peptides/proteins affects cell growth. Some aptamers have been shown to bind to specific cell receptors and in one case thioaptamers were developed that bind the primary receptor for hyaluronic acid [37]. As this receptor plays an important function in tumour growth, it is possible that sgc8c may also bind similar receptors on the ovarian cancer cells, which may be the cause of their inherent cytotoxicity.…”
Section: Aptamer Effect On Phenen Cytotoxicity and Uptakementioning
confidence: 99%